Dose reduction in computed tomography of the chest: image quality of iterative reconstructions at a 50% radiation dose compared to filtered back projection at a 100% radiation dose - May, Matthias; Eller, A.; Stahl, Christian; Wuest, W.; Scharf, M.; Hammon, Matthias; Dankerl, P.; Schlechtweg, Philipp; Allmendinger, T.; Sedlmair, M.; Schmidt, B.; Uder, Michael; et al. (Röfo-Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
The aim of this study was to evaluate the potential of iterative reconstruction (IR) in chest computed tomography (CT) to reduce radiation exposure. The qualitative and quantitative image quality of standard reconstructions with filtered back projection (FBP) and half dose (HD) chest CT data reconstructed with FBP and IR was assessed.52 consecutive patients underwent contrast-enhanced chest CT on a dual-source CT system at 120 kV and automatic exposure control. The tube current was equally split on both tube detector systems. For the HD datasets, only data from one tube detector system was utilized. Thus, FD and HD data was available for each patient with a single scan. Three datasets were reconstructed from the raw data: standard full dose (FD) images applying FBP which served as a reference, HD images applying FBP and IR. Objective image quality analysis was performed by measuring the image noise in tissue and air. The subjective image quality was evaluated by 2 radiologists according to European guidelines. Additional assessment of artifacts, lesion conspicuity and edge sharpness was performed.Image noise did not differ significantly between HD-IR and FD-FBP (p = 0.254) but increased substantially in HD-FBP (p < 0.001). No statistically significant differences were found for the reproduction of anatomical and pathological structures between HD-IR and FD-FBP, subsegmental bronchi and bronchioli. The image quality of HD-FBP was rated inferior because of increased noise.A 50 % dose reduction in contrast-enhanced chest CT is feasible without a loss of diagnostic confidence if IR is used for image data reconstruction. Iterative reconstruction is another powerful tool to reduce radiation exposure and can be combined with other dose-saving techniques.o?Iterative reconstructions allow for image noise and artifact reduction.o?Comparable image data can thus be attained even at 50 % radiation dose.o?Diagnostic confidence remains unaffected.
EVALuna2:14376